2013
DOI: 10.3390/foods2040488
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Profile of Soil-Free versus In-Soil Grown Lettuce and Intervention Methodologies to Combat Pathogen Surrogates and Spoilage Microorganisms on Lettuce

Abstract: Aquaponics is an effective method to practice sustainable agriculture and is gaining popularity in the US; however, the microbial safety of aquaponically grown produce needs to be ascertained. Aquaponics is a unique marriage of fish production and soil-free produce (e.g., leafy greens) production. Fish are raised in fresh water tanks that are connected to water filled beds where fruits and vegetables are grown. The fish bi-products create nutrient-rich water that provides the key elements for the growth of pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 15 publications
(20 reference statements)
4
24
0
Order By: Relevance
“…However, Sirsat et al (2015) reviewed the published literature related to the prevalence of microorganisms on food products sold at farmers' markets and highlighted that in some instances there was higher bacterial prevalence on food items from farmers' markets when compared to their retail super market counterparts. For instance, several independent studies published from to 2014 demonstrated that bacterial concentrations on leafy greens purchased at farmers' markets were significantly higher than retail super markets (Sirsat & Neal, 2013;Scheinberg, Doores, & Cutter, 2013;Soendjojo, 2012;Su, 2014). Therefore, contrary to the currently available evidence, positive safety perceptions of farmers' markets were widely held among surveyed consumers.…”
Section: Discussionmentioning
confidence: 99%
“…However, Sirsat et al (2015) reviewed the published literature related to the prevalence of microorganisms on food products sold at farmers' markets and highlighted that in some instances there was higher bacterial prevalence on food items from farmers' markets when compared to their retail super market counterparts. For instance, several independent studies published from to 2014 demonstrated that bacterial concentrations on leafy greens purchased at farmers' markets were significantly higher than retail super markets (Sirsat & Neal, 2013;Scheinberg, Doores, & Cutter, 2013;Soendjojo, 2012;Su, 2014). Therefore, contrary to the currently available evidence, positive safety perceptions of farmers' markets were widely held among surveyed consumers.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the results have shown higher bacterial prevalence on food items purchased from farmers' markets. The results showed that lettuce obtained from the farmers' market had significantly higher (10 3 log CFU/g) E. coli concentrations compared to the lettuce obtained from the grocery stores (Sirsat and Neal, 2013). The results demonstrated the presence of Campylobacter jejuni on six vegetable types obtained from the outdoor farmers' market.…”
Section: Farmers' Market Microbial Researchmentioning
confidence: 86%
“…Indicator microbes and pathogenic bacteria, such as E. coli and Salmonella spp., if present in aquaponic systems, most probably originate from warm-blooded animals, such as birds, since these enteric bacteria are transient in fish gut microflora (Sugita et al, 1996). As in all crop production systems cross-contamination is possible, but the risk in aquaponics is greatly reduced when compared with field crops (Sirsat and Neal, 2013). Studies from Oman (Goddard et al, 2015), USA (Fox et al, 2012) and Canada (Chalmers, 2004) have reported negative tests across numerous aquaponic farms for E. coli and Salmonella spp.…”
Section: Safetymentioning
confidence: 99%